(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Soft tissue injuries are prevalent musculoskeletal conditions that often require comprehensive management strategies for optimal recovery. Physiotherapy plays a crucial role in promoting tissue healing, restoring function, and mitigating disability associated with these injuries. Additionally, the integration of anti-inflammatory medications enhances the efficacy of physiotherapeutic interventions by alleviating pain and reducing inflammation. This article reviews the role of anti-inflammatory medications in physiotherapy for soft tissue injuries, highlighting their mechanisms of action, benefits, considerations, and synergies with rehabilitation protocols. Nonsteroidal anti-inflammatory drugs (NSAIDs) and corticosteroids are the main classes of medications utilized, targeting key inflammatory pathways to facilitate early mobilization and participation in rehabilitation exercises. While offering significant symptomatic relief, the use of anti-inflammatory medications requires careful consideration of potential risks and contraindications, emphasizing the importance of judicious prescribing and monitoring. Integration of pharmacotherapy with tailored physiotherapy protocols enables a comprehensive approach to soft tissue injury management, ultimately optimizing patient outcomes and functional restoration.